Time intervals between the end of A wave to the onset of QRS in relation to age in a group of healthy Singaporean people. (12th October 2011) - Qiong, Huang Fei; Liang, Zhong; Lay-kheng, Tan; Lay-hong, Chua Yvonne; San, Tan Ru; Zeepin, Ding
Abstract : Objective: The aims of our study are to describe the time intervals between the end of transmitral flow A velocity and onset of QRS on the ECG, stroke volume of left atrium at end of T wave and onset of P wave on the ECG in normal subjects, and examine the effect of age on these parameters. Methods: Total of 138 normal healthy adults (22–78 years old) were enrolled. The transmitral flow E and A wave were recorded by Doppler echocardiography. The time intervals from the end of transmitral flow A velocity to the onset of QRS on the ECG, diameters of mitral annulus at the end of T wave and the onset of P wave on the ECG, VTI of the mitral valve E and A were measured. We calculated the SV of mitral valve E and A as formulas: SV=0.785*diameter of mitral 2 *VTI. Results: Showed in table 1 . Conclusions: SV-A increased and the time intervals between the end of A wave to the onset of QRS decreased reflected the deterioration of left atrial conduit function and increased pump function due to reduced left ventricular diastolic function with age.